State of the pheto-placenteral complex in pregnant women with obstetric pathology and burdened reproductive history - Н. П. Гончарук (Publishing House TRILIST, 2019)
Purpose of the study. To study the fetoplacental system (FPS) status in women with obstetric pathology and a burdened reproductive history. Materials and methods. The study included 500 pregnant women who were divided into four groups: I - 150 women with an uterus scar, II - 150 women after assisted reproductive technologies, III - 150 women with anomalies in labor, 0 - 50 healthy pregnant women without obstetric pathology and without burdened reproductive history. The level of PPS hormones was determined in serum, depending on type of obstetric pathology and characteristics of the reproductive history. The study of hormonal indicators was carried out in the pregnancy dynamics. Fetus state was evaluated with a cardiotocographic study. Results. Increase in placental lactogen level was observed in the pregnancy dynamics in women with obstetric pathology and a burdened reproductive history, but its growth in 21-30 and 31-40 weeks was less than in pregnant women without obstetric pathology and without a burdened reproductive history. Dynamics of the estriol and estradiol levels in the blood in all groups in the gestational age of 21-30 weeks was characterized by approximately the same levels of decrease compared with healthy pregnant women without obstetric complications. Decrease in progesterone secretion was observed in all pregnant women with obstetric pathology and burdened reproductive history. Dynamics of it level in the blood serum during pregnancy up to 20 weeks, 21-30 weeks and 31-40 weeks showed a decrease. This is a reflection of changes in the PPS state in general and leads to fetus deterioration. Conclusions. There is a feto-placental insufficiency in pregnant women with obstetric pathology and with a burdened reproductive history that is manifested by inhibition of the hormonal function of the feto-placental complex and proceeds against the background of fetal heart rate changes. Identified changes require the preventive and therapeutic measures aimed at correcting the fetus impaired condition and changes in FPS